Pelatihan Resiliensi Berbasis Peer Support pada Siswa Korban Bullying di SMP Negeri Semarang - Maryati Maryati; E Puspitasari; N Sukesi (Jurnal Pengabdian Bidang Kesehatan, 2025)
Bullying is a serious problem that negatively affects students’ mental health, self-esteem, and academic achievement. Resilience functions as a protective factor that enables victims of bullying to remain adaptive despite adverse experiences. Peer support has been shown to enhance self-confidence, social competence, and psychological resilience among adolescents. This community service program aimed to strengthen students’ resilience through peer support training at SMP Negeri Semarang in July 2025. A total of 18 students identified by school counselors as bullying victims participated in three training sessions: (1) education on bullying and resilience, (2) resilience skills training including emotional regulation, problem solving, and positive thinking, and (3) peer support group formation. The Connor-Davidson Resilience Scale (CD-RISC-10) was used to measure resilience before and after the intervention. Findings indicated an increase in average resilience scores from 21.6 to 29.6, representing a 37% improvement. Qualitative observations revealed enhanced self-confidence, improved emotional regulation, and stronger social support from peers. These results demonstrate that peer support-based resilience training is effective in improving students’ psychological adaptability. The intervention can serve as a school-based psychosocial strategy to foster mental well-being among adolescents, particularly those who have experienced bullying.